Pemodelan Sederhana Persamaan Laplace Pada Potensial Menggunakan Finite Difference - Meldra, Delia; Mardiansyah, Yopy (Greeners: Journal of Green Engineering for Sustainability, 2024)
Geo-electricity is a methods to measure potential in the earth’s surface. Laplace equation’s second orde is used in natural potential measurement. Finite difference method is used to solve this Laplace equation to get numeric solution. The solution figures the distribution of source potential that gotten from many sides of modeling domain.